Influence of psychological conditions on the level of creative imagination - Kryshtanovych, Svitlana; Bilyk, Valentyna; Matvienko, Olena; Stepanenko, Liudmyla; Tsvietkova, Hanna (Creativity Studies, 2022)
The main purpose of the study is to determine the influence of psychological conditions on the development of creative imagination. As a result of research, we applied several key methods that allowed us to achieve this goal. First of all, it is a method of theoretical analysis and synthesis. Also, methods of correlation analysis and a number of empirical methods were used for the existing experimental group (observation, conversation, questionnaire, testing). The analysis of the psychological conditions of the correlation matrix showed that there is a noticeably high connection between the influences of psychological conditions on the development of creative imagination, thereby confirming our assumption. According to the results of the study of the development of creative imagination, the dominance of the middle and low levels of its development was established. In addition, the criteria of creative imagination were diagnosed, which included the originality of images, flexibility of images, performance of images, speed of the created image. It was found that the most developed is the originality of images, the least developed is the performance of images.